MODERN APPROACHES TO THE MANAGEMENT OF PREGNANT WOMEN WITH LARGE UTERINE FIBROIDS - Сергей Владимирович Баринов; Юлия Игоревна Тирская; Оксана Вячеславовна Лазарева; Татьяна Владимировна Кадцына; Юрий Игоревич Чуловский; Екатерина Александровна Фрикель (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - to improve the results of management of pregnant women with large uterine leiomyoma by introducing an integrated approach. Materials and methods. 120 pregnant women with large uterine fibroids (more than 8 cm) were observed. The main group was observed using an integrated approach: micronized progesterone intravaginally combined with the installation of an obstetric pessary. The comparison group was conducted in accordance with current clinical guidelines. According to indications, myomectomy was performed during pregnancy. Depending on the myomectomy performed, the groups were divided into subgroups. Results. In the main group, against the background of the combined method of management, the threat of miscarriage was observed less frequently, the frequency of preterm birth (PTB) significantly decreased, fetal malnutrition and premature abruption of a normally located placenta were less frequently observed, and the need for myomectomy during pregnancy arose half as often. Myomectomy additionally reduced the number of PRs in subgroups by two to five times compared to patients who did not undergo myomectomy. Conclusion. The developed algorithm for the management of pregnant women with large uterine leiomyomas made it possible to significantly prolong pregnancy to full term and reduce the number of organ-loss operations. The developed technique for performing myomectomy during pregnancy allows us to minimize surgical risks, promotes the formation of a full-fledged scar on the uterus, and prolongs pregnancy.